Hydrological and hydrochemical supporting conditions for Irish calcareous fen vegetation - Bijkerk, Elisabeth Wilhelmina (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2023)
Calcareous fens are listed in Annex 1 of the European Union (EU) Habitats Directive (Council Directive 92/43/EEC, habitat code 7230, 7210 and 7140) as habitats requiring special conservation measures, including the designation of suitable sites as Special Areas of Conservation (SACs). They are largely groundwater fed wetlands, being located in topographic hollows and fed by springs or seepages of water that has been in contact with mineral ground. Their principal source of nutrients is from surface or groundwater and the substrate is an alkaline to slightly acidic peat soil. The hydrogeological dynamics and hydrochemical signature supports small sedge and brown moss communities in a mosaic of different habitats. It is acknowledged however that currently no studies of these systems exist from which the environmental supporting conditions could be determined. Therefore, the objective of this study is to investigate hydrological and hydrochemical controls that support Irish alkaline fen habitat. An intensive multidisciplinary monitoring programme was set up in the following four fen sites containing calcareous fen covering an eco-hydrological gradient from intact to highly degraded conditions: 1) Ballymore, Co. Westmeath, with intact habitat, 2) Pollardstown, Co. Kildare, degraded by drainage and nutrient pollution, 3) Scragh Bog (fen), Co. Westmeath, with near intact habitat threatened by nutrient pollution and 4) Tory Hill, Co. Limerick, highly degraded by drainage. Hydrological and hydrochemical was collated in order to build conceptual eco-hydrological models to represent both temporal and spatial variability in each geological setting. Data collected from surveyed good quality fen vegetation was used a representative for these models. Higher concentrations of nutrients were found in the sediments at depth compared to the phreatic water table. This suggests that the vegetation is using up the incoming nutrients and thereby ending up in an organic form. In the natural life cycle of the vegetation, annual decay allows for these nutrients to come back out into solution and disperse into the underlying till substrate. Statistical analysis of the surface water nutrient concentrations associated with the different fen habitat types suggested typical maximum values of 37 ?g-P/l for dissolved reactive phosphorus, 382 ?g-P/l total phosphorus, 0.57 mg-N/l for ammonia, 0.17 mg-N/l for total oxidised nitrogen and 2.01 mg-N/l for total dissolved nitrogen. It also seemed that specific vegetation required a minimum threshold of nutrients from groundwater flow in order to survive. The hydraulic gradients suggested that the incoming water from the aquifer enters the fen via discrete conduits straight into the phreatic zone by flowing through the underlying substrate in a more diffuse manner. Equally, in terms of water level, the field investigations suggest that the mean annual water levels are required to stay above ground level in order to support healthy fen vegetation with a threshold water level envelope of between 29 mm to 277 mm above ground level. Furthermore in order to maintain good quality fen vegetation environmental conditions should not change the vertical hydraulic gradients by more than 0.4 during a hydrological year.
APPROVED
Keywords: Hydrochemistry; Water level; Water quality; Ecology; Fen; Calcareous fen; Hydrology; Wetland; Nutrients; Conceptual model; Phreatic zone; Groundwater; Habitat quality; Drainage; Nutrient pollution; Fen vegetation